2011
DOI: 10.1111/j.1365-2230.2011.04127.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of Blastocystis hominis isolates in urticaria: a case–control study

Abstract: Blastocystis hominis is a common intestinal parasite, with a prevalence in developing countries of up to 50%. The aim of this study was to investigate the association of this parasite with urticaria by determining the genotypic isotypes in the Egyptian population. In total, 54 patients with urticaria and 50 controls were enrolled in the study. Stool samples were examined and assessed by PCR. The parasite was detected in a significantly higher number (P < 0.001) of the patient group than the control group. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 7 publications
1
23
1
3
Order By: Relevance
“…However, a number of case reports recently showed that Blastocystis hominis infection is associated with chronic urticaria [5][6][7]. The study of Zuel-Fakkar et al reported that Blastocystis hominis was found in 60.6% of patients with urticaria, whereas no parasite was isolated in healthy controls [8]. In general, urticaria is a very common skin disorder that can have immune, non-immune or idiopathic causes [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, a number of case reports recently showed that Blastocystis hominis infection is associated with chronic urticaria [5][6][7]. The study of Zuel-Fakkar et al reported that Blastocystis hominis was found in 60.6% of patients with urticaria, whereas no parasite was isolated in healthy controls [8]. In general, urticaria is a very common skin disorder that can have immune, non-immune or idiopathic causes [9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to aspecific gastrointestinal symptoms, studies associated the parasite with cutaneous disorders and chronic or acute urticaria [Vogelberg et al 2010;Hameed et al 2011;Zuel-Fakkar et al 2011;Verma and Delfanian, 2013]. These diseases were correlated with the presence of Blastocystis sp.…”
Section: Blastocystis Sp Is Associated With Various Clinical Symptommentioning
confidence: 99%
“…These diseases were correlated with the presence of Blastocystis sp. belonging to the ST2 [Vogelberg et al 2010] or ST3 [Zuel-Fakkar et al 2011] in the patient stools. An association was also found between urticaria and amoeboid forms of a ST3 isolate [Katsarou-Katsari et al 2008].…”
Section: Blastocystis Sp Is Associated With Various Clinical Symptommentioning
confidence: 99%
“…Metronidazole is the suggested drug of choice, although failures of this drug in eradicating the organism are common (275,407,409). Cotrimoxazole, nitazoxanide, and a combination of paromomycin and metronidazole have also been used (222,485). A recent study found extensive differences in drug sensitivities among two clinically important zoonotic subtypes (subtypes 4 and 7) and identified four new potential therapeutic options against Blastocystis spp., namely, mefloquine, cotrimoxazole (trimethoprim-sulfamethoxazole) (1:2), ornidazole, and furazolidone; the study also confirmed the antiprotozoal activities of 10 compounds already reported to be effective against Blastocystis spp.…”
Section: Blastocystis Speciesmentioning
confidence: 99%